Formulasi Strategi Badan Amil Zakat Nasional (Baznas) Kota Bogor Dengan Business Model Canvas Dan Balanced Scorecard Sebagai Dasar Pemikiran Pengembangan Organisasi - Bayu Purnama Putra; Mukhaer Pakkanna (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
The city of Bogor, which is a service city, can collect more zakat. In order to strengthen the institution, professional ZIS management is needed. Bogor City National Amil Zakat Agency needs to make a strategy formulation. This study uses descriptive qualitative analysis methods with two management tools, namely Business Model Canvas (BMC) and Balanced Scorecard (BSC). Strategy formulation, Bogor City National Amil Zakat Agency with BMC consists of nine blocks, namely customer segments, value proportions, Channels ie, volunteers and UPZ, customer relations, revenue streams, vital resources, key activities, key partnerships, cost structures. Next, make a strategy map with BSC in four perspectives. Financial/social perspective, namely improving the welfare of Muslims in the City of Bogor, increasing ZIS income, and increasing the welfare of mustahik. The customer perspective is to increase awareness of ZIS, increase the collection and distribution of ZIS, increase the circulation of funds of the people towards a just economic life and increase the dignity of the mustahik towards prosperity and prosperity. Internal business process perspective that is socializing every step of BAZ through publication media, developing da'wah, developing volunteer networks, enhancing amiline capabilities, developing muzakki potential through various forums, building government and business support, building partnership relationships with various Islamic social institutions and programs. Learning and Growth Perspectives, namely disciplining financial reports and management of zakat, increasing the competence of staff and volunteers, improving the application of governance and SIMBA, and improving facilities and infrastructure.